Swedish and Danish typo-morphology – The historical approaches and new conceptualizations for informing urban design - Stojanovski, Todor; Strandbygaard, Sofie Kirt; Maudsley, Ann; Abarkan, Abdellah (Lodz University of Technology Press, 2023)
Neighbourhood typologies can be used to inform city planning and urban design. This paper looks at historical approaches and new conceptualizations in Sweden and Denmark to discuss implication for urban design practices. There is a long typo-morphological tradition in Sweden, however in Denmark it is seldom used as a method of analysis. This paper starts with describing three historical Swedish typo-morphological approaches. The first is historic-architectural emphasizes architectural styles. The second focuses on classifying neighbourhood types by physical attributes. The third argues that the Swedish neighbourhood typology describes not only physical form but also social structure. The Danish application of neighbourhood types is more generic and made with the purpose of comparing numeric data with urban planning tendencies. It considers three major morphological urban structures and uses them to make combinations, as most neighbourhoods are hybrids of types. This paper discusses differences between well-established Swedish neighbourhood typology versus the Danish generic typology and concludes with implication for urban design practices and designing Transit-Oriented Developments (TODs). Practicing architects and urban designers can apply morphological research and both detailed or generic local neighbourhood typologies can be very useful conceptualizations.
Keywords: urban morphology; typo-morphology; neighbourhood types; urban design; Transit-Oriented Development (TOD); morfologia miast; typo-morfologia; typy dzielnic; projektowanie urbanistyczne; rozwój zorientowany na transport (TOD)